2008
DOI: 10.1183/09031936.00135907
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide predicts lung function decline in difficult-to-treat asthma

Abstract: A subset of patients with asthma is known to have progressive loss of lung function despite treatment with corticosteroids. The aim of the present study was to identify risk factors of decline in forced expiratory volume in one second (FEV1) in patients with difficult-to-treat asthma.In total, 136 nonsmoking patients with difficult-to-treat asthma were recruited between 1998 and 1999. Follow-up assessment was performed 5-6 yrs later in 98 patients. The predictive effect of clinical characteristics and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
6
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 32 publications
7
71
6
2
Order By: Relevance
“…Higher FeNO values, perhaps due to the higher reported inducible nitric oxide synthase expression in severe asthmatic epithelial cells, have been associated with a more exacerbation prone phenotype in severe asthma, as well as more rapid decline in FEV1 [76,[91][92][93]. In addition, higher levels of oxidative stress have been associated with a reduction in superoxide dismutase and s-nitrosothiol depletion [94,95].…”
Section: Activation Of Innate Immune Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher FeNO values, perhaps due to the higher reported inducible nitric oxide synthase expression in severe asthmatic epithelial cells, have been associated with a more exacerbation prone phenotype in severe asthma, as well as more rapid decline in FEV1 [76,[91][92][93]. In addition, higher levels of oxidative stress have been associated with a reduction in superoxide dismutase and s-nitrosothiol depletion [94,95].…”
Section: Activation Of Innate Immune Pathwaysmentioning
confidence: 99%
“…Prospective studies of lung function decline in severe asthma are limited, but suggest that male sex, smoking, increased FeNO and African ancestry are contributors, while interestingly, allergic status may be protective [93,126].…”
Section: Physiologymentioning
confidence: 99%
“…Because this study had a cross-sectional design, it is as yet unclear whether this represents merely an association or whether abnormalities in small airways may be used as a predictor of subsequent exacerbations. In addition, VAN VEEN et al [43] had observed that exhaled NO predicts lung function decline in severe asthmatics during 5 yrs of prospective follow-up [43]. Interestingly, this relationship was only found in subjects with baseline FEV1 .80% pred, whereas no relationship was found in subjects with FEV1 f80%, suggesting that these findings may be related to small airways rather than larger airways [43].…”
Section: Relevance Of Small Airways In Asthmamentioning
confidence: 84%
“…Further studies are needed to determine the nature of the interaction between NO and TLC in asthma, but the current study shows that FE NO is associated with hyperinflation in asthma. Furthermore, FE NO in severe asthma might reflect airway-remodeling processes (48,49). Because many of the variables that are related to NO are also related to severity, relationships between variables and FE NO were also evaluated within severity group by multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%